2019
DOI: 10.1186/s12882-019-1435-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of default mode functional connectivity in individuals with end-stage renal disease and mild cognitive impairment

Abstract: Background Mild cognitive impairment (MCI) occurs frequently in many end stage renal disease (ESRD) patients, may significantly worsen survival odds and prognosis. However, the exact neuropathological mechanisms of MCI combined with ESRD are not fully clear. This study examined functional connectivity (FC) alterations of the default-mode network (DMN) in individuals with ESRD and MCI. Methods Twenty–four individuals with ESRD identified as MCI patients were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…In our previous study, independent component analysis of rs-fMRI revealed that ESRD patients exhibited abnormalities in the default-mode network of the brain and had decreased functional connectivity of the posterior cingulate gyrus (12). The finding from the present study that the ALFF values of the bilateral anterior and middle cingulate gyrus were significantly decreased in ESRD patients further supports previous findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our previous study, independent component analysis of rs-fMRI revealed that ESRD patients exhibited abnormalities in the default-mode network of the brain and had decreased functional connectivity of the posterior cingulate gyrus (12). The finding from the present study that the ALFF values of the bilateral anterior and middle cingulate gyrus were significantly decreased in ESRD patients further supports previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…One possibility is that damage to the posterior cingulate gyrus occurs later than damage to the anterior and middle cingulate gyri in ESRD patients. Another possibility is that the neural functional impairment in the posterior cingulate gyrus is a manifestation of other factors resulting from the decline of nonspontaneous neural activity in ESRD patients, such as the decrease in functional connectivity found in previous study (12). The second factor is the interference of other diseases.…”
Section: Discussionmentioning
confidence: 87%
“…In our study, creatinine and urea levels in patients with ESRD were positively correlated with the z -values of FC between the aMPFC and PCC. This is a surprising finding that completely contradicts previous research ( 20 , 35 ). To the best of our knowledge, long-term hemodialysis patients have elevated creatinine and urea levels, and the accumulation of uremic toxins results in a series of brain injuries, including neurotoxicity, neuroinflammation, blood–brain barrier injury, oxidative stress, microvascular changes, apoptosis, and brain metabolic dysfunction ( 45 ).…”
Section: Discussioncontrasting
confidence: 94%
“…In line with our findings, Ni et al (19) found through ICA that ESRD patients showed decreased FC in the PCC, precuneus, and MPFC, with further reduction in the MPFC with the development of minimal nephrotic encephalopathy. Similarly, Lu et al (35) reported that significantly decreased FC of the DMN was observed in the PCC and Pcu, as well as in the MPFC, in the ESRD group with mild cognitive impairment. However, a previous study (21) using the PCC and vMPFC as seeds found that some other regions also had decreased FC with the PCC or vMPFC, such as the thalamus, middle temporal gyrus, and anterior cingulate gyrus, which was inconsistent with our results.…”
Section: Disrupted Cortical Hubs In Patients With Esrdmentioning
confidence: 72%
“…As the posterior default-mode network (DMN) hub, individuals with ESRD showed decreased functional connectivity in the PCC, which were closely related to vital cognitive functions, such as memory. 22,48 In fact, posterior leukinopathy is not uncommon in ESRD patients who undergo dialysis, 49 and PCC, as the posterior DMN hub, is often involved in the complications of cerebrovascular autoregulation damage, endothelial injury, and elevated plasma concentration of natriuretic peptide. 48 Moreover, some investigators have also highlighted the importance of progressive functional connectivity density decreased of the ACC in patients with ESRD from healthy controls to minimal nephrotic encephalopathy that may be correlated to cognitive deficits.…”
Section: Brain Regions and Cognitive Impairmentmentioning
confidence: 99%